A Scoping Review of Different Ways of Thinking in Children - Elisa Jones Arango; Shane Costello; Christine Grové (Behavioral Sciences, 2018)
Despite the growing interest in differences in thinking, much less is known about differences in how children think and how they come to think. The aim of this scoping review is to map out the key concepts underpinning the conceptual boundaries of children’s (5–12 years of age) individual differences in thinking. The scoping review identified eight papers for analysis; all of which were set in an educational context. The findings presented inconclusive results regarding learning and thinking differences related to students’ academic achievement. This review has identified two main drawbacks with this research area. Firstly, there is little consensus between the models employed to understand the different ways children think. To further place these findings into context we look at conceptualisations of individual differences, where individuality is considered a process of stable characteristics interacting with more dynamic structures. This analysis highlights the second drawback, previous research has solely focused on exploring thinking characteristics that are not stable and are therefore subject to change depending on the context. The review found that there is little to no research which explores thinking preferences in children that are consistent across contexts and time. Moreover, there was no research identified that explored the impact of differences in thinking outside the educational domain, such as children’s wellbeing. Further research is required to identify the more stable characteristics that reflect and capture children’s different ways of thinking.